Understanding the inguinal sinus in sheep (Ovis aries)—Morphology, secretion, and expression of progesterone, estrogens, and prolactin receptors - Alexandre-Pires, G. (2017)
info:eu-repo/grantAgreement/FCT/5876/147283/PT Funding for this work was provided by the Portuguese Foundation for Science and Technology (FCT) with co-participation of European Union Fund (FEDER) through the research project UID/CVT/00276/2013. The authors present special thanks to Sandra Carvalho and Rosario Luis (Histology Dept., FMV) and Gloria Nunes (Immunology Dept., FCM) for technical assistance.